TOTAL FLAVONOIDS CONTENT IN ACIDIFIED EXTRACT OF FLOWERS AND LEAVES OF GARDENIA (GARDENIA JASMINOIDES ELLIS) - Saptarini, Nyi Mekar; Herawati, Irma Erika; Permatasari, Uli Yana (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Background: Gardenia (Gardenia jasminoides Ellis) contains secondary metabolites which responsible for pharmacological activities such as flavonoids. Objective: The aims of this study were to determine the total flavonoids content (TFC) in the flowers and leaves of gardenia (G. jasminoides Ellis) which macerated with acidified ethanol. Method: The method was the colorimetric of a colored complex between flavonoid with aluminum chloride. Results: The results showed that the highest TFC in the flowers (0.078% w/w) was obtained in a mixture solvent of ethanol and acetic acid, whereas in the leaves (0.090% w/w) was obtained in ethanol. Conclusion: There is no correlation between acidified ethanol and TFC in gardenia flowers and leaves. Keywords: Maceration, Acidified ethanol, Colorimetric, Aluminum chloride.